Representasi Konflik Israel-Palestina dan Gaya Bahasa pada Puisi Karya Halimi Zuhdy: Perspektif Stilistika Morris - Nur, Muhammad; Qalbi, Nur Latifatul; Hidayatullah, Muhammad Syarif (Maliki Interdisciplinary Journal, 2025)
Poetry, as a manifestation of linguistic art, plays a crucial role in reflecting social and human realities. In the context of the prolonged conflict in Palestine, poetry functions as a voice for the voiceless, immortalizing suffering, and evoking global empathy. This research deeply analyzes the stylistics of two poems by Halimi Zuhdy: ’Palestine; A Declaration of Humanity, Amidst the Tumult of Crimson Blood’ and ’Poetry of the Declaration of UIN Malang Leaders’. By adopting a comprehensive stylistic approach—encompassing diction, imagery, concrete words, figures of speech, and rhyme—this study aims to uncover how the poet utilizes the richness of language. This linguistic utilization not only serves to depict the atrocities of the Israeli-Palestinian conflict but also to voice resistance, hope, and a universal call for humanity. The analysis specifically connects each stylistic element with the social and historical facts of the conflict in Palestine, demonstrating how poetic language becomes a sharp instrument of critique, a concrete documentation of suffering, and a profound reflection on geopolitical conditions. The findings indicate that these two poems represent powerful and effective artistic expressions that foster an understanding of the Palestinian issue’s complexity and encourage collective reflection on endangered humanitarian values.